Dendritic cell expression of the transcription factor T-bet regulates mast cell progenitor homing to mucosal tissue - Alcaide, Pilar (The Rockefeller University Press, 2007)
The transcription factor T-bet was identified in CD4(+) T cells, and it controls interferon γ production and T helper type 1 cell differentiation. T-bet is expressed in certain other leukocytes, and we recently showed (Lord, G.M., R.M. Rao, H. Choe, B.M. Sullivan, A.H. Lichtman, F.W. Luscinskas, and L.H. Glimcher. 2005. Blood. 106:3432–3439) that it regulates T cell trafficking. We examined whether T-bet influences homing of mast cell progenitors (MCp) to peripheral tissues. Surprisingly, we found that MCp homing to the lung or small intestine in T-bet(−/−) mice is reduced. This is reproduced in adhesion studies using bone marrow–derived MCs (BMMCs) from T-bet(−/−) mice, which showed diminished adhesion to mucosal addresin cellular adhesion molecule–1 (MAdCAM-1) and vascular cell adhesion molecule–1 (VCAM-1), endothelial ligands required for MCp intestinal homing. MCp, their precursors, and BMMCs do not express T-bet, suggesting that T-bet plays an indirect role in homing. However, adoptive transfer experiments revealed that T-bet expression by BM cells is required for MCp homing to the intestine. Furthermore, transfer of WT BM-derived dendritic cells (DCs) to T-bet(−/−) mice restores normal MCp intestinal homing in vivo and MCp adhesion to MAdCAM-1 and VCAM-1 in vitro. Nonetheless, T-bet(−/−) mice respond vigorously to intestinal infection with Trichinella spiralis, eliminating a role for T-bet in MC recruitment to sites of infection and their activation and function. Therefore, remarkably, T-bet expression by DCs indirectly controls MCp homing to mucosal tissues.